The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s43032-020-00350-z
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Exosomal miR-214-3p Targeting CCN2 Contributes to Endometriosis Fibrosis and the Role of Exosomes in the Horizontal Transfer of miR-214-3p

Abstract: Endometriosis (EMs) is defined as the presence of tissue which somewhat resembles endometrial glands and stroma outside the uterus, and elicits fibrosis. Fibrosis is the main factor resulting in pain and infertility, while the aetiology of endometrial fibrosis is unknown. There is strong evidence from numerous experiments showing that connective tissue growth factor (CCN2) plays a central role in fibrogenesis. Exosomal miR-214-3p can regulate the expression of CCN2 through binding to complementary sites in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Zhao et al found that miR-194-5p repressed cell progression and promoted cell apoptosis of ectopic endometrial cells by modulating STAT1/mTOR signaling pathway [ 15 ]. Moreover, exosomal miR-214-3p suppressed cell fibrosis in EM by targeting CCN2, suggesting that miR-214-3p may be a biomarker for EM therapy [ 16 ]. miR-206 has been reported to be a therapy biomarker in CC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al found that miR-194-5p repressed cell progression and promoted cell apoptosis of ectopic endometrial cells by modulating STAT1/mTOR signaling pathway [ 15 ]. Moreover, exosomal miR-214-3p suppressed cell fibrosis in EM by targeting CCN2, suggesting that miR-214-3p may be a biomarker for EM therapy [ 16 ]. miR-206 has been reported to be a therapy biomarker in CC [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), especially exosomes, have been well-established to deliver microRNAs (miRNAs), proteins, and lipids, and the cargos have been assumed to work cooperatively to modulate tumor microenvironment [ 9 ]. Intriguingly, evidence exists suggesting that exosomes secreted by ectopic endometrial stromal cells could restrict the fibrosis in EMs by delivering a typical miRNA, miR-214 [ 10 , 11 ]. Further, another miRNA, miR-30c, has been highlighted for notably downregulated expression in ectopic and eutopic endometriosis tissues [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-15a-5p was poorly expressed in EMS. Similarly, level of exosomal miR-214-3p in EMS patients’ serum was lower than that of non-EMS patient [ 19 ]. Moreover, overexpression of miR-214 offers an alternative therapeutic approach for EMS fibrosis [ 20 ].…”
Section: Discussionmentioning
confidence: 99%